Context manipulation in police interviews: a field experiment - Kelly, Christopher E. (Journal of experimental criminology, 2021)
Objectives Recent writing and research on interrogation has highlighted the potential importance of the physical context in which the interview takes place. Whereas manuals and self-reports from police investigators indicate how they can leverage the space to maximize control over subjects, arguments for non-coercive manipulation of the room context are emerging in the literature. For instance, in laboratory settings, positive effects on interview outcomes have been demonstrated where alterations were made to the room’s physical space. Method In collaboration with a large American police department, interviews with witnesses to serious violent crime were randomly assigned to an experimental or control context. The experimental room was altered to create a space that was intended to be more comfortable than the control context of a standard interrogation room. Results Seventy-seven post-interview questionnaires were completed by detectives and 50 were completed by witnesses that included items related to the interpersonal dynamics and how much the witnesses contributed to the investigation. Although not significantly different, witnesses in the experimental room reported it as being a more comfortable setting, and there is evidence that interpersonal dynamics were actually better in the control context. Conclusions As the first of its kind in a police setting, this study demonstrates that it is possible to manipulate the perceptions of space within an interrogation room; however, the manipulations did not have the intended effects based on the principles of implicit cognition. Implications for future research and practice are discussed.